Tata Communications Ltd : innovating a global business model - Williamson, Peter, active 2013; Wilson, Keeley (London : University of Cambridge, Judge Business School, 2013)
From his office in Singapore, Vinod Kumar, Managing Director of Tata Communications Limited (Tata Comm.) and CEO of Tata Communications Limited Group, began the regular weekly meeting of his executive team with a flick of the Telepresence "start" button. His team of senior executives was spread between Mumbai, Montreal, Matawan-NJ, Hong Kong, and London as well as Singapore, but as the video wall lit up they appeared as if they were just across the boardroom table. Tata Comm. had come a long way since it entered the Tata group in 2002, but as 2013 opened he believed that company was what he called "an inflection point" in its journey: a future where the key to success would be to innovatively use its infrastructure and global knowledge and relationships to provide not just communications capacity, but solutions and transformational capabilities to its customers.
Originally published in Williamson, P., & Wilson, K. (2013). Tata Communications Ltd: Innovating a Global Business Model. Cambridge, UK: University of Cambridge, Judge Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Kumar, Vinod, -- active 2013.; Tata Communications Limited; Tata Communications Limited Group; International business enterprises -- Singapore